Pathology in clinical practice : 50 case studies - Newell, Barry A. T. (London : Hodder Education, 2009)
This title features 50 structured clinical scenarios to help readers consolidate existing knowledge about pathology. Each case is based on a clinical situation that pulls together the key pathological, radiological and clinical aspects of a condition, while the questions and answers highlight diagnostic avenues--
pt. 1. Symptoms -- pt. 2. Signs -- pt. 3. Investigations -- pt. 4. Treatment -- pt. 5. Complex management.
Includes indexes.
Keywords: Pathology -- Case studies; Pathology -- Problems, exercises, etc; Diagnosis, Laboratory -- Case studies